Response to: Evaluating strategies to manage and endure challenging behaviors in mucopolysaccharidoses - Hoffmann, Frederik; Ries, Markus (Orphanet journal of rare diseases, 2021)
The mucopolysaccharidoses (MPS) are a group of rare, genetic, lysosomal storage disorders characterized by progressive, multisystemic accumulation of glycosaminoglycans. Individuals with severe MPS often present with significant neurological involvement and may exhibit challenging behaviors, including hyperactivity, aggression, and sleep disturbance. These behaviors can cause adverse outcomes and necessitate the development of specific measures to support affected families. Through an analysis of the results reported by Hoffmann et al. in their recent study, this letter outlines important factors that must be considered when evaluating the impact of challenging behaviors associated with MPS, including treatment history, age, sibling and family relationships, the feasibility of daily caregiving, and caregiver burden. These recommendations can help guide future studies to identify the most effective coping strategies to support families of people with MPS who have challenging behaviors.
Gesehen am 25.05.2021